Does Reporting Heterogeneity bias the Measurement of Health Disparities? - Teresa Bago d'Uva; Eddy van Doorslaer; Maarten Lindeboom; Owen O'Donnell; Somnath Chatterji (Tinbergen Institute, 2006)
Heterogeneity in reporting of health by socio-economic and demographic characteristics potentially biases the measurement of health disparities. We use anchoring vignettes to identify socio-demographic differences in the reporting of health in Indonesia, India and China. Homogeneous reporting by socio-demographic group is rejected and correcting for reporting heterogeneity tends to reduce slightly estimated disparities in health by education (not China) and to increase those by income. But the method does not reveal substantial reporting bias in measures of health disparities.
Keywords: D30; D31; I10; I12; 330; health measurement; vignettes; self-reported health; reporting heterogeneity